Improved data envelopment analysis models for evaluating interval efficiencies of decision-making units - Azizi, Hossein; Jahed, Rasul (Computers & industrial engineering, 2011)
► We present two perspectives for obtaining bounds of efficiency with crisp data. ► The optimistic view uses the efficiency frontier, giving the best efficiency. ► The pessimistic view uses the inefficient frontier, giving the worst efficiency. ► The efficiency interval presents all possible evaluations from various viewpoints. ► This interval provides the decision maker with all possible values of efficiency. In a recent article, Wang et al. [Wang, N. S., Yi, R. H., & Wang, W. (2008). Evaluating the performances of decision-making units based on interval efficiencies. Journal of Computational and Applied Mathematics, 216, 328–343] proposed a pair of interval data envelopment analysis (DEA) models for measuring the overall performances of decision-making units (DMUs) with crisp data. In this paper, we demonstrate that interval DEA models face problems in determining the efficiency interval for each DMU when there are zero values for every input. To remedy this drawback, we propose a pair of improved interval DEA models which make it possible to perform a DEA analysis using the concepts of the best and the worst relative efficiencies. Two numerical examples will be examined using the improved interval DEA models. One of the examples is a real-world application about 42 educational departments in one of the branches of the Islamic Azad University in Iran that shows the advantages and applicability of the improved approach in real-life situations.